Toward the design of efficient adsorbents for Hg2+ removal: Molecular and thermodynamic insights. Issue 15 (3rd May 2020) - Forgionny, Angélica; Acelas, Nancy Y.; Jimenez‐Orozco, Carlos; Flórez, Elizabeth
Abstract: A systematic DFT study was performed to evaluate the effect of oxygenated functional groups for Hg 2+ adsorption in aqueous systems. This work includes several aspects usually neglected in many current works, namely, ground‐state multiplicity, solvation effects, establishment of thermodynamic parameters, atomic charge transfer, and modeling of infrared spectra. In addition, two carbonaceous models were studied to account for both the effect of the carbonaceous matrix and the oxygenated functional groups on the Hg 2+ binding. Adsorption energies indicated that Hg 2+ adsorption on the unsaturated model is favored in the following order: phenol > lactone > semiquinone > carboxyl, whereas for the saturated model, the Hg 2+ adsorption energy decrease order is: carboxyl > semiquinone > lactone. Thermodynamic parameters confirmed that the adsorption process is spontaneous (unsaturated model), while the infrared spectra provided an insight at the atomic level about the experimentally reported bands. Our results contributed to a deeper understanding of the current experimental information on the effect of the surface functional groups on the Hg 2+ adsorption over carbonaceous materials as different active sites can be present on oxygenated carbonaceous materials for metal adsorption. The results also create new ways to improve the performance of adsorption capability of mercury and other pollutants. Abstract : A systematic DFT study was performed to evaluate the effect of oxygenated functional groups on Hg 2+ adsorption in aqueous systems. This work includes several aspects usually avoided in many current works, namely, ground‐state multiplicity, solvation effects, establishment of thermodynamic parameters, atomic charge transfer, and modeling of infrared spectra. Our results contributed to a deeper understanding of Hg 2+ removal, creating new ways to improve the performance of adsorption capability of mercury and other pollutants.